Identity and Access Management in the Cloud - Pratik Jain (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud computing has revolutionized the way businesses and organizations operate, enabling scalable, flexible, and cost-effective IT infrastructures. However, as the reliance on cloud services grows, so do the challenges related to securing sensitive data and systems. Identity and Access Management (IAM) plays a crucial role in ensuring that only authorized users can access cloud resources. This paper explores the fundamental concepts of IAM in the cloud, focusing on its components, authentication mechanisms, and authorization processes. It discusses how IAM systems are structured, the various mechanisms used to authenticate users, and how access